ANALISIS KEMAMPUAN BERPIKIR KREATIF PADA PEMBELAJARAN IPA BERBASIS INKUIRI TERBIMBING - Riyadna Krismanita; Ahmad Qosyim (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aims to describe effectiveness of creative thinking training in junior high school science learning through guided inquiry. This study used a qualitative descriptive research method by analyzing four training practices for creative thinking skills in science-based guided inquiry learning that had been carried out by previous researchers. Object of research in this study is an article or journal related to guided inquiry-based learning to improve creative thinking skills in junior high school science learning. Data collection technique used literature study. Data analysis technique in this study used content analysis techniques. Results obtained from this study are the research of Kurniati et al. (2018) dan Suhartini et al. (2016) more effective in training students' creative thinking in science learning based on guided inquiry, by practicing all aspects of creative thinking which are then aligned with the guided inquiry stage. Meanwhile, the two other studies have shortcomings because the creative thinking aspect is not trained as a whole and there are aspects of creative thinking that are not in line with the guided inquiry stage.